2020
DOI: 10.1097/01.aoa.0000652952.24035.d4
|View full text |Cite
|
Sign up to set email alerts
|

Time From Neuraxial Anesthesia Placement to Delivery is Inversely Proportional to Umbilical Arterial Cord pH at Scheduled Cesarean Delivery

Abstract: (Am J Obst Gynecol. 2019;220:389.e1–389.e9) While the maternal risks of cesarean delivery are well documented in the literature, less is known about the risks to the fetus. Neuraxial block-related hypotension and maternal obesity have been found to contribute to uterine hypoperfusion and umbilical arterial pH depression. Examining the time between spinal anesthesia placement and delivery could provide insight into these risks to the fetus awaiting cesarean delivery. The aim of this study was to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…There is a link between the drop of maternal blood pressure (BP) and fetal acidosis [ 3 ]. Yet, the impact of the duration of hypotension episodes is not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There is a link between the drop of maternal blood pressure (BP) and fetal acidosis [ 3 ]. Yet, the impact of the duration of hypotension episodes is not well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In their 2019 study, Rimsza et al [28] reported that longer spinal anesthesia to delivery time and uterine incision to delivery time were associated with decreased umbilical arterial pH in planned term cesarean deliveries. Eff orts to minimize predelivery time following spinal anesthesia injection could reduce the frequency of unanticipated neonatal acidemia.…”
Section: Issn: 2640-5628mentioning
confidence: 99%
“…Neonatal morbidity, including low 5-minute Apgar scores (<7), umbilical cord arterial pH < 7.2, base excess ≤8 mmol/L, and neonatal intensive care unit admissions are seen more often in obese women who undergo cesarean delivery. Hypotension during spinal anesthesia, and prolonged puncture time for regional anesthesia is more pronounced in obese women, and has been shown to cause lower umbilical cord pH in obese women undergoing scheduled cesarean delivery [40,41]. Women who are super-obese at the time of delivery have a 20% chance of neonatal intensive care unit admission [26].…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…Still, dose reductions for spinal anesthesia have not been proven beneficial in obese patients [54]. The obese patient is at risk for a higher number of punctures at time of spinal placement, simply due to spinal cord distance from skin [41,55]. Ultrasound guided regional anesthesia placement has been shown to reduce number of punctures in obese women [56].…”
Section: Anesthetic Considerationsmentioning
confidence: 99%